Engineered exosome-mediated delivery of functionally active miR-26a and its enhanced suppression effect in HepG2 cells - Liang G (Dove Medical Press, 2018)
Gaofeng Liang,1,2,* Shu Kan,2,* Yanliang Zhu,3 Shuying Feng,1 Wenpo Feng,1 Shegan Gao1,4 1Medical College, Henan University of Science and Technology, Luoyang, China; 2Department of Biomedical Engineering, University of California Berkeley, California, CA, USA; 3State Key laboratory of Bioelectronics, School of Biological Science and Medical Engineering, Southeast University, Nanjing, 4Henan Key Laboratory of Cancer Epigenetics, The First Affiliated Hospital of Henan University of Science and Technology, Luoyang, China *These authors contributed equally to this work Introduction: Exosomes are closed-membrane nanovesicles that are secreted by a variety of cells and exist in most body fluids. Recent studies have demonstrated the potential of exosomes as natural vehicles that target delivery of functional small RNA and chemotherapeutics to diseased cells. Methods: In this study, we introduce a new approach for the targeted delivery of exosomes loaded with functional miR-26a to scavenger receptor class B type 1-expressing liver cancer cells. The tumor cell-targeting function of these engineered exosomes was introduced by expressing in 293T cell hosts, the gene fusion between the transmembrane protein of CD63 and a sequence from Apo-A1. The exosomes harvested from these 293T cells were loaded with miR-26a via electroporation. Results: The engineered exosomes were shown to bind selectively to HepG2 cells via the scavenger receptor class B type 1–Apo-A1 complex and then internalized by receptor-mediated endocytosis. The release of miR-26a in exosome-treated HepG2 cells upregulated miR-26a expression and decreased the rates of cell migration and proliferation. We also presented evidence that suggest cell growth was inhibited by miR-26a-mediated decreases in the amounts of key proteins that regulate the cell cycle. Conclusion: Our gene delivery strategy can be adapted to treat a broad spectrum of cancers by expressing proteins on the surface of miRNA-loaded exosomes that recognize specific biomarkers on the tumor cell. Keywords: exosome, gene delivery, miR-26a, HepG2 cells